Characteristics of an ideal practice educator: Perspectives from practice educators in diagnostic radiography, nuclear medicine, nutrition and dietetics, occupational therapy and physiotherapy and radiation therapy. Issue 4 (November 2016) - Francis, A.; Hills, C.; MacDonald-Wicks, L.; Johnston, C.; James, D.; Surjan, Y.; Warren-Forward, H.
Abstract: Background: Practice education is a compulsory component of health programs with practice educators playing a critical role in the education of students. Practice educator characteristics may positively or negatively affect student learning in practice settings. This study aimed to identify characteristics of the ideal practice educator that lead to successful practical experiences as perceived by current practice educators working in the Australian context of diagnostic radiography, nuclear medicine, nutrition and dietetics, occupational therapy, physiotherapy and radiation therapy. Methods: All practice educators (n = 1063) on the University of Newcastle Practice Educator Database were invited to participate in this prospective, cross-sectional, descriptive study via online link or paper format. Results: There was a 52% response rate. The five most valued characteristics were feedback skills, non-judgemental, professionalism, clarity and listening skills. The five least valued characteristics were scholarly activity, respect for students' autonomy, well-prepared, availability and being a role model. Comparisons between disciplines, genders, ages, years in practice and levels of supervisory experience indicated some statistically significant differences, though actual differences were small. Discussion: Overall there was a high degree of agreement within and between disciplines on the characteristics of the ideal practice educator. The top five skills could be classed as generic skills and not specific clinical and practice skills, thus formal training and certification schemes may enhance practice educator competence. Highlights: The most important characteristics were feedback skills and non-judgmental . The least important characteristics were scholarly activity and respects student autonomy . Female educators valued all characteristics except scholarly activities as being more important. Older participants valued availability, and scholarly activity less than the younger age group. High level of agreement across all disciplines.